The Effect of Anti-Addiction Training on Attitudes Towards Substance Users and Sense of Compassion (Third Sector Social Economic Review, 2025)
The purpose of this study is to investigate the effect of addiction prevention education on the attitudes and compassion of individuals with substance use disorders. The research method employed a pre-test and post-test control group quasi-experimental design. Participants were students aged 20-21 studying at the Faculty of Sports Sciences in a province of Turkey during the 2023-2024 academic year. A total of 53 participants took part, with 28 students (7 female, 21 male) in the experimental group and 25 students (5 female, 20 male) in the control group. A 12-week addiction prevention education program was implemented for the experimental group, while no intervention was made for the control group. The inclusion of pre-tests and post-tests, along with the requirement for training, has resulted in limitations on the number of participants in the study. Data were collected using the Compassion and Attitude Scale for Individuals Using Addictive Substances. The Cronbach's Alpha value indicating the reliability of the compassion scale was found to be 0.85, and the Cronbach's Alpha value indicating the reliability of the attitude scale was found to be 0.94. According to the findings of the study, the addiction prevention education resulted in a statistically significant improvement in attitudes toward substance-using individuals in the experimental group compared to the control group (p
Keywords: Struggle Against Addiction; Substance Addiction; Compassion Training; Social Impact